2019
DOI: 10.21037/atm.2019.12.18
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hypoxia-inducible factor prolyl hydroxylase inhibitor roxadustat on renal anemia in non-dialysis-dependent chronic kidney disease: a systematic review and meta-analysis

Abstract: Background: Renal anemia is a severe complication of chronic kidney disease (CKD) and may worsen its prognosis. Roxadustat is the only oral hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI) that has been proved effective to treat renal anemia. However, effects of roxadustat on non-dialysis-dependent CKD (NDD-CKD) have yet to be supported by evidence-based medicine.Methods: Based on the databases of PubMed, EMBASE and Web of Science by 12 April 2019 (CRD42019133225), a meta-analysis of randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
3
18
1
3
Order By: Relevance
“…Although previous meta-analyses (28)(29)(30)(31)(32)(33)(34) have compared the efficacy and safety of roxadustat vs. placebo or ESA, the results showed that roxadustat was more effective than placebo and noninferior to ESA in correcting anemia in CKD patients. However, evidence for the results is still lacking and several new clinical trials have been conducted to compare roxadustat with placebo or ESA for the treatment of anemia in NDD-CKD or DD-CKD patients.…”
Section: Discussionmentioning
confidence: 95%
“…Although previous meta-analyses (28)(29)(30)(31)(32)(33)(34) have compared the efficacy and safety of roxadustat vs. placebo or ESA, the results showed that roxadustat was more effective than placebo and noninferior to ESA in correcting anemia in CKD patients. However, evidence for the results is still lacking and several new clinical trials have been conducted to compare roxadustat with placebo or ESA for the treatment of anemia in NDD-CKD or DD-CKD patients.…”
Section: Discussionmentioning
confidence: 95%
“…However, only two phase III trials were enrolled in two of previously published meta-analyses (Liu et al, 2020;Zheng et al, 2020). Conclusions about the efficacy and safety of roxadustat were based on phase II trials exclusively in other meta-analyses (Zhong et al, 2018;Jia et al, 2019;Hu et al, 2020). In addition, the number of studies and sample size of patients included in above meta-analyses was relatively small, not exceeding 9 studies and 1,010 participants, which might have an impact on the strength of meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Roxadustat, a potent, reversible, HIF-PHI that mimics the natural response to hypoxia results in target genes involved in erythropoiesis [ 31 33 ]. The meta-analysis of randomized controlled trials showed that Roxadustat can improve hemoglobin levels and iron metabolism in both dialysis-dependent and non-dialysis-dependent chronic kidney disease [ 34 , 35 ]. However, its long term efficacy and safety needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%